Recent Progress in Optoelectronic Synapses for Artificial Visual‐Perception System. Issue 3 (1st October 2020) - Han, Xun; Xu, Zhangsheng; Wu, Wenqiang; Liu, Xianhu; Yan, Peiguang; Pan, Caofeng
Abstract : The human visual system undertakes most of the information perceiving tasks, and nearly 80% of the perceived information is obtained via the visual system. The basic functions of the human visual system can be emulated by neuromorphic visual‐perception systems in the light region from UV to near‐IR. An optoelectronic synapse served as the basic unit of the neuromorphic visual‐perception system is required to combine photosensing function and synaptic element. In addition, optoelectronic synapses demonstrate the prospective advantage of large bandwidth, ultrafast signal transmission, and low electrical energy loss, which is expected in the photonic signal‐triggered computing. This work reviews recent progress in the optoelectrical synapses. Device architectures and working mechanisms are discussed. The applications in the artificial visual‐perception system for image memorization and pattern recognition are reviewed. The main challenges and opportunities of optoelectrical synapses are also presented. Abstract : An optoelectronic synapse with the advantages of ultrafast signal transmission, large bandwidth, and low electrical energy loss has attracted much attention for neuromorphic computing. This review summarizes recent advances in the optoelectronic synapse, including the device architectures, working mechanisms, and their applications in the artificial visual‐perception system for image memorization and pattern recognition.